Prevalence of undernutrition and its associated factors among pregnant women attending antenatal care service in public hospitals in Mogadishu, Somalia - Abdullahi Ahmed Tahlil; Naimo Abdikadir Abdillahi; Asho Jama Adam; Anisa Abdi Ali; Fadumo Mohumed Ahmed; Zeynab Osman Abdi; Maryan Muhudin Ali; Muno Abdulle Hubur; Hassan Ibrahim Nor; Mohamed Abdelrahman Mohamed; Liban Abdi Ali; Osman Mohamed Mohamud (PLoS ONE, 2026)
Introduction Maternal undernutrition remains a major public health concern globally, particularly in Somalia, where conflict, poverty, and food insecurity exacerbate nutritional deficiencies. Undernutrition during pregnancy poses serious risks to both maternal and fetal health, including increased maternal mortality, low birth weight, and adverse developmental outcomes. Despite its critical implications, there is limited evidence on the burden and associated factors of maternal undernutrition in Somalia. This study assessed the prevalence and associated factors of undernutrition among pregnant women attending antenatal care (ANC) services in public hospitals in Mogadishu. Methods A facility-based cross-sectional study was conducted among 734 pregnant women attending antenatal care (ANC) services in public hospitals in Mogadishu. Participants were selected using a multistage sampling technique. Data were collected using interviewer-administered questionnaires and anthropometric measurements. Undernutrition was assessed using mid-upper arm circumference (MUAC < 23 cm), a measure commonly applied in clinical and humanitarian settings. Household food insecurity was assessed using the Household Food Insecurity Access Scale (HFIAS). Data were analyzed using SPSS version 26, and multivariable logistic regression was performed to identify factors associated with undernutrition at a significance level of p < 0.05. Results The prevalence of maternal undernutrition was 75.7% (95% CI: 72.6%–78.9%). Factors independently associated with undernutrition included maternal age 25–31 years (AOR = 2.61, 95% CI: 1.28–5.30) and 32–38 years (AOR = 2.18, 95% CI: 1.04–4.55), tertiary education (AOR = 3.43, 95% CI: 1.89–6.21), employee occupation (AOR = 6.38, 95% CI: 2.90–14.04), private business occupation (AOR = 9.79, 95% CI: 4.27–22.43), large household size (AOR = 1.96, 95% CI: 1.34–2.88), urban residence (AOR = 2.40, 95% CI: 1.39–4.15), household monthly income < USD 500 (AOR = 1.98, 95% CI: 1.33–2.94), lack of latrine facility (AOR = 2.00, 95% CI: 1.23–3.26), second (AOR = 8.59, 95% CI: 5.29–13.97) and third trimester (AOR = 6.91, 95% CI: 2.97–16.08), primigravidity (AOR = 2.29, 95% CI: 1.52–3.45), contraceptive use (AOR = 1.98, 95% CI: 1.34–2.90), substance use (AOR = 2.79, 95% CI: 1.93–4.04), and severe household food insecurity (AOR = 1.76, 95% CI: 1.01–3.08). However, some associations with large effect sizes should be interpreted with caution, as they may reflect residual confounding, small subgroup sizes, or model instability. Conclusion This study revealed a high prevalence of maternal undernutrition among pregnant women attending ANC services in Mogadishu, with multiple factors found to be associated with undernutrition. These findings highlight the need for targeted, multi-sectoral interventions to improve maternal nutrition through enhanced food security, health education, and access to nutrition-sensitive and nutrition-specific services. Targeted strategies such as supplementation programs, nutrition counseling, and improved water, sanitation, and hygiene (WASH) services are critical to mitigating maternal undernutrition and achieving Sustainable Development Goals related to maternal and child health.